Leverage Demand-side Policies for Energy Security - Bento, N. (EDITS/CMCC Global Webinar, Fondazione CMCC - Centro Euro-Mediterraneo sui Cambiamenti Climatici, 2024)
Energy security is a top priority for governments, companies, and households because energy systems and the critical functions that they support are threatened by disruptions from wars, pandemics, climate change, and other shocks (1). More often than not, governments rely on policies focused on energy supply to enhance energy security while generally ignoring demand-side possibilities. Further, the indicators traditionally used to measure energy security are also tilted toward the supply side; this fails to capture the full spectrum of vulnerability to energy crises. Energy security assessments need to reflect the wider benefits of security-related interventions more accurately. To that end, we develop a systematic approach to measuring the energy security impacts of policy interventions that explicitly considers energy demand (buildings, transport, and industry). We determine that demand-side actions outperform conventional supply-side approaches at making countries more resilient.